TAILORED BASELLA ALBA MUCILAGE-BASED BIPOLYMERIC HYDROGEL BEADS FOR CONTROLLED RELEASE OF DICLOFENAC SODIUM - CHOWDHURY, MOUMITA; KUMAR DE, PINTU (International Journal of Applied Pharmaceutics, 2023)
Objective: The present investigation aims to convert the underutilized Basella alba mucilage (BAM) into a smart carrier by formulating its bipolymeric hydrogel beads for the controlled release of Diclofenac sodium (DFS). Methods: At first, mucilage from the stem and fruits of Basella alba was extracted, isolated, and evaluated. Basella alba mucilage was chemically modified to its carboxymethyl derivative to improve its physicochemical properties. Single and bipolymeric hydrogel beads of carboxymethylated Basella alba mucilage (CBAM) and Sodium carboxymethyl cellulose (SCMC) were formulated by the Ionotropic gelation method using aluminium chloride (AlCl3) as a cross-linking agent. A four-factor I-optimal response surface design was used to optimize the formulations. Drug and excipient compatibility was studied by Fourier transform infrared spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC) study. Scanning electron microscopy (SEM) was done to reveal the surface morphology. In vitro release of the drug in phosphate buffer (pH 6.8) and acidic buffer (pH 1.2) were compared for all the formulations. The effect of various formulation parameters on the release of the drug was studied, and the best-fitting model for release kinetics was determined. Results: The degree of carboxymethylation was found to be 0.565±0.05. The bipolymeric beads were found to release 14% drug in 2 h in acidic media, minimize the release of the drug in the stomach to avoid the harsh effects of DFS and then provide controlled release in the intestine, releasing 80-90% of the drug in 10 h. The release kinetics followed the Hixon Crowell model, which suggests an erosion of the matrix to release the drug. Conclusion: The bipolymeric hydrogel beads of tailored Basella alba mucilage were found to control the release of Diclofenac sodium.